2021
DOI: 10.1002/adhm.202001806
|View full text |Cite
|
Sign up to set email alerts
|

Noble Metal Nanomaterials for NIR‐Triggered Photothermal Therapy in Cancer

Abstract: It is of great significance to develop anticancer therapeutic agents or technologies with high degree of specificity and patient compliance, while low toxicity. The emerging photothermal therapy (PTT) has become a new and powerful therapeutic technology due to its noninvasiveness, high specificity, low side effects to normal tissues and strong anticancer efficacy. Noble metal nanomaterials possess strong surface plasmon resonance (SPR) effect and synthetic tunability, which make them facile and effective PTT a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
145
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(158 citation statements)
references
References 136 publications
2
145
0
Order By: Relevance
“…PTA can eradicate tumors by rapidly converting NIR light energy into heat, and therefore, these agents have attracted remarkable interest [34]. In recent decades, most of the effort directed to PTA has focused on metal nanomaterials because of their highly effective optical absorption and photothermal conversation.…”
Section: Discussionmentioning
confidence: 99%
“…PTA can eradicate tumors by rapidly converting NIR light energy into heat, and therefore, these agents have attracted remarkable interest [34]. In recent decades, most of the effort directed to PTA has focused on metal nanomaterials because of their highly effective optical absorption and photothermal conversation.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some skin allergies have also been noted with the use of colloidal noble metal nanoparticles [119]. In addition, Zhu et al [120] have found that noble metals have been applied as a multifunctional cancer therapy because of their remarkable surface plasmon responses. Furthermore, a number of hazardous pollutants are also being generated as byproducts due to the rapid development of chemical industries.…”
Section: Impact Of Nanoparticles Of Human Health and Enviromentsmentioning
confidence: 99%
“…In addition, light-induced therapies have been also taken advantage of noble metal nanoparticles to selectively enhance therapy performance. In the last few years, noble metal-based nanoparticles have risen as one of the most promising alternatives to selectively promote light-triggered therapies such as photothermal therapy (PTT) [41,42] or PDT [43]. Moreover, some photocatalysts may also transform intracellular GSH into GSSG via h + consumption.…”
Section: Introductionmentioning
confidence: 99%